Research on Vietnamese Local Governance - Son, Nguyen Van (Journal of Ecohumanism, 2024)
One of the characteristics of local governance is the interaction between government agencies and people in the process of social development governance. Accordingly, people want to participate more in government governance activities; the government mobilizes people’s participation to effectively promote local resources to serve development strategies. This study analyzes the characteristics of local governance in terms of people’s participation; analyzes the practice of people’s participation in local governance activities in Vietnam. The author conducted a survey of 300 people from 3 localities representing 3 regions of Vietnam, including Thai Nguyen province (North), Quang Nam province (Central), Ben Tre province (South) to collect information and analyze, evaluate the practice of people’s participation in social development governance activities of local government agencies. The survey results have helped the author to assess the reality and have a basis to conclude that: People participate directly and indirectly in local governance activities, but are limited in the level of direct participation. From this research result, the author discusses the research problem, which is to expand the rights of people to participate in local governance activities.